FEATURES OF STRATEGIC MANAGEMENT OF THE COMPETITIVENESS OF A CAR SERVICE COMPANYS - DRAZHNYTSIA, Sergii; DARIUSH, Sergii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In this article, the authors specify the essence and significance of strategic management of the enterprise’s competitiveness, as the main means of making managerial decisions and coordinating the enterprise’s activities in order to ensure its profitable and uninterrupted functioning in the long term. The authors provide a generalized definition of strategic management and its functions, the main tasks and issues of strategic management of the competitiveness of car service enterprises, as well as factors influencing this process. Also, in the article, the authors analyzed and divided the auto service enterprises operating in the local market into groups, depending on the degree of their strategic development. Based on the analysis, the authors identified a number of problems and unfavorable factors that prevent and restrain the use of strategic management methods by auto service enterprises, and also proposed specific strategic alternatives for improving their strategic development.